Amino acid salt-driven planar hybrid perovskite solar cells with enhanced humidity stability. (May 2019) - Yun, Seong-Cheol; Ma, Sunihl; Kwon, Hyeok-Chan; Kim, Kyungmi; Jang, Gyumin; Yang, Hyunha; Moon, Jooho
Abstract: While hybrid perovskites have great potential as light-absorbing materials, they suffer from moisture-induced instability. Herein, we added the amino acid iodide salt-based molecular crosslinker p -aminobenzoic acid (PABA∙HI) to a perovskite precursor solution to enhance the humidity stability. The rigid molecular structure of PABA∙HI played an important role in determining the crystal orientation, trap density, and photovoltaic performance of the perovskite solar cells (PVSCs). PABA∙HI can effectively interact with the Pb-I framework via hydrogen bonds, enhancing the crosslinking efficiency compared with freely rotating flexible molecular crosslinkers. Kelvin probe force microscopy in conjunction with Raman analysis confirmed the presence of PABA∙HI at the grain boundaries; thus, stable quasi-two-dimensional perovskite existed along the grain boundaries, passivating the grain boundaries and improving the moisture stability. The PABA∙HI-added PVSCs having a power-conversion efficiency (PCE) of 17.4% retained 91% of their initial PCE when stored for 312 h at a relative humidity of 75% at 25 °C, whereas a pristine cell with a PCE of 16.4% only retained 37% of its initial value. Our findings clearly indicate that the amino acid salt as a rigid molecular crosslinker improved not only the photovoltaic performance but also the stability against moisture. Graphical abstract: The addition of rigid molecular crosslinker p -aminobenzoic acid iodide (PABA∙HI) enhanced the stability of perovskites against moisture by forming quasi-two-dimensional perovskite along grain boundaries. Perovskite solar cells with PABA∙HI retained 91% of their initial power-conversion efficiency of 17.4% under a relative humidity of 75% at 25 °C after 312 h of exposure under dark condition.fx1 Highlights: The rigid molecule, p -aminobenzoic acid iodide (PABA∙HI), can interact effectively with perovskite grains so as to increase crystal orientation. The PABA∙HI molecules are mainly located along grain boundaries passivating defects and forming quasi-2D perovskite, resulting in enhanced PCE. The moisture and thermal stability of PVSCs with PABA∙HI are significantly improved.